Homo ludens: proeve eener bepaling van het spel-element der cultuur - Huizinga, Johan 1872-1945 (Haarlem Tjeenk Willink, 1952)
In Homo Ludens, Johan Huizinga defines play as the central activity in flourishing societies. He identifies five characteristics of play: it is free; it is not “ordinary” or “real” life; it is distinct from “ordinary” life both as to locality and duration; it creates order; it is connected with no material interest, and from it no profit can be gained.With cross-cultural examples from the humanities, business, and politics, Huizinga examines play in all its diverse guises—as it relates to language, law, war, knowledge, poetry, myth, philosophy, art, and much more. As he writes, “Civilization is, in its earliest phases, played. It does not come from play like a baby detaching itself from the womb: it arises in and as play, and never leaves it.”
Originally published in 1938
Displayed as part of the 'Game On' exhibition during Erfgoeddag on 27 April 2025
Keywords: Philosophy